Muslim Immigrant Consumer Awareness And Policy Implications Of Halal Food In Malaysia - Fatkhur Rohman Albanjari; Nugraheni Fitroh Syakarna; Jihan Nabila Zahara; Mazuri Binti Abd. Ghani (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
This study attempts to investigate the awareness of halal food consumption among muslim immigrants in Malaysia. This is because Malaysia is the halal center of the world. Qualitative research approach case study method with data collection techniques through interviews, direct observation and documentation with a total of 9 Muslim immigrants in Malaysia. The location of the study is centered in Kampung Baharu. The results showed that Muslim immigrants' consumer awareness is high due to policies carried out by the Malaysian government such as halal labeling and halal policies that are able to increase their awareness. Providing halal assurance to consumers, both domestic and international, the government has created a business ecosystem conducive to the growth of the halal industry. The Malaysian government has given full support to the development and promotion of Malaysia as the world's halal center. This support is manifested in various programs and policies that support the halal industry.